2014
DOI: 10.1177/1553350614535860
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Cyanoacrylate Embolization for Refractory Gastrointestinal Fistulae

Abstract: Cyanoacrylate embolization of nearly all types of refractory gastrointestinal fistulae is a feasible and harmless technique. Prospective controlled studies are required to support the available evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Although our results were obtained from a retrospective series, in our opinion, it would be possible to hypothesize that the lack of complications might be at least partly derived from our long experience in treating variceal bleeding with this product that has been largely documented in digestive endoscopy[29,32-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Although our results were obtained from a retrospective series, in our opinion, it would be possible to hypothesize that the lack of complications might be at least partly derived from our long experience in treating variceal bleeding with this product that has been largely documented in digestive endoscopy[29,32-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Avalos-Gonzalez et al reported earlier fistula closure and decreased morbidity in the fibrin-treated group compared to controls [ 54 ]. A meta-analysis reviewing 14 studies that evaluated the efficacy of cyanoacrylate reported a success rate of 81% [ 55 ]. Despite the high success rate, high-output gastrointestinal fistulas are less likely to be successfully closed by sealant alone.…”
Section: Individual Endoscopic Techniquesmentioning
confidence: 99%
“…For surgical treatment of patients with intestinal fistula must be carried nutritional recovery, replacement and stabilization of electrolytes, identification of the fistulous path, drainage adjacent and along the fistula and abscess to allow full closure thereof and the abdominal wall. [59,60]. Depending on the site of the fistula, replacement of fistula output varies.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Normal intestinal motility and function generally return once abdominal sepsis is controlled and fluid and electrolyte imbalances are corrected. If the fistula location is such that enteric access and alimentation are possible, enteral nutrition can be instituted and parenteral nutrition phased out [59]. By using a combination of approaches, adequate nutrition can be maintained throughout the patient's course [1].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation